A dynamic pathway analysis approach reveals a limiting futile cycle in N-acetylglucosamine overproducing Bacillus subtilis - Yanfeng Liu (Nature Portfolio, 2016)
Rate-limiting steps in synthetic metabolic pathways are difficult to identify. Here, the authors monitor metabolite dynamics and apply kinetic modelling during the start-up phase of the Bacillus subtilisGlcNAc pathway to discover a futile cycle, allowing them to identify a more productive strain.